2012
DOI: 10.1084/jem.20121044
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase 1 regulates nuclear reprogramming and promotes iPSC generation without c-Myc

Abstract: Parp1 can replace c-Myc to promote induced pluripotent stem cell (iPSC) generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 47 publications
5
85
0
Order By: Relevance
“…Our group and others have recently demonstrated that PARP1 is also involved in the efficient generation of iPSCs, which is probably due to PARP1‐dependent chromatin remodeling and epigenetic modulation 8, 11, 27. Here, we established strong physical and functional links between PARP1 and CHD1L and their roles in regulating the chromatin states of stemness genes.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Our group and others have recently demonstrated that PARP1 is also involved in the efficient generation of iPSCs, which is probably due to PARP1‐dependent chromatin remodeling and epigenetic modulation 8, 11, 27. Here, we established strong physical and functional links between PARP1 and CHD1L and their roles in regulating the chromatin states of stemness genes.…”
Section: Discussionsupporting
confidence: 61%
“…The role of PARP1 in cell reprogramming has been demonstrated in recent studies, although the underlying mechanism of the PARP1‐driven stemness signature in promoting reprogramming efficiency remains unclear. CHD1L, a chromatin modulator that regulates nucleosome sliding, has been demonstrated to interact with PARP1 during DNA repair 22, 23, and our previous results demonstrated an interaction between CHD1L and PARP1 during cell reprogramming 27. Microarray analysis and WB results showed that the expression level of Parp1 parallels the expression of Chd1l , one of the ATP‐dependent chromatin‐remodeling enzymes active during the process of reprogramming, in reprogrammed cells at various stages of reprogramming (from Day 0.5 to Day 12; Fig.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Poly(ADP-ribose) (PAR) is a reversible post-translational modification involved in multiple essential cellular processes including DNA damage, transcriptional control, and stem cell identity (Beneke, 2012; Chiou et al, 2013; Doege et al, 2012; Hassa and Hottiger, 2008; Ji and Tulin, 2010; Krishnakumar and Kraus, 2010a; Ogino et al, 2007; Tallis et al, 2013). Using NAD + as a substrate, poly(ADP-ribose) polymerases (PARPs) polymerize ADP-ribose subunits onto acceptor proteins, forming large, negatively charged polymers of varying length (Schreiber et al, 2006; Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PARP1, localized primarily to the nucleus, is the most abundant family member in humans (Vyas et al, 2013; Wang et al, 2012) and has been mainly examined in the context of base excision repair (Sousa et al, 2012). Recently PARP1 was implicated in other DNA repair pathways as well as in pathways outside of DNA repair such as transcription (Ji and Tulin, 2013; Krishnakumar and Kraus, 2010b) and stem cell identity (Chiou et al, 2013; Doege et al, 2012; Ogino et al, 2007). The details of its involvement in any of these pathways remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%